Language learning through critical pedagogy in a "Brave New World" - DERİNCE, ZEYNEP MİNE (My University, 2011)
After passing their university entry exam, students who wish to study a subject at one of the Turkish universities offering English-medium courses attend a one-year preparatory class. At the end of this, they need to pass an English language proficiency exam in order to be admitted to their chosen course of study. The existing curriculum for such preparatory classes is designed to be taught in English only and very much oriented towards passing the concluding standardised language proficiency exam at the end. This approach does not teach the students any of the skills they will need for their further study, such as how to think critically or to question their own conditioning and political attitudes. Using a different methodology, the author of this paper conducted an in-class project with students learning English in a Turkish state university's preparatory class. The project was carried out within a framework of critical pedagogy and used both Turkish and English during the phases of research and discussion. Evaluating the students' own reflections on the experience as well as their final presentations which were prepared in English, the author suggests that the critical pedagogy approach in combination with a maximum use of students' means of expression and language resources led to a more meaningful learning experience - both for the students and for herself - as well as a more efficient and lasting English language proficiency. © 2011 Springer Science+Business Media B.V.
Keywords: Conditioning; Critical pedagogy; Curriculum; Dialogue; English language teaching and learning; Turkey